Research progress on the pattern recognition receptors involved in porcine reproductive and respiratory syndrome virus infection - Xu, Yulin; Ding, Luogang; Zhang, Yuyu; Ren, Sufang; Li, Jianda; Liu, Fei; Sun, Wenbo; Chen, Zhi; Yu, Jiang; Wu, Jiaqiang (Frontiers in Cellular and Infection Microbiology, 2024)
Porcine reproductive and respiratory syndrome (PRRS) is one of the most economically devastating infectious diseases of pigs globally. The pathogen, porcine reproductive and respiratory syndrome virus (PRRSV), is an enveloped positive-stranded RNA virus, which is considered to be the key triggers for the activation of effective innate immunity through pattern recognition receptor (PRR)-dependent signaling pathways. Toll-like receptors (TLRs), RIG-I-like receptors (RLRs), C-type lectin receptors (CLRs), NOD-like receptors (NLRs) and Cytoplasmic DNA receptors (CDRs) are used as PRRs to identify distinct but overlapping microbial components. The innate immune system has evolved to recognize RNA or DNA molecules from microbes through pattern recognition receptors (PRRs) and to induce defense response against infections, including the production of type I interferon (IFN-I) and inflammatory cytokines. However, PRRSV is capable of continuous evolution through gene mutation and recombination to evade host immune defenses and exploit host cell mechanisms to synthesize and transport its components, thereby facilitating successful infection and replication. This review presents the research progress made in recent years in the study of these PRRs and their associated adapters during PRRSV infection.